NEUROETHICAL CONSIDERATIONS IN NEUROMARKETING: A FRAMEWORK FOR RESPONSIBLE RESEARCH AND APPLICATION - Khairul Putra; Lukmanul Hakim; Dahrul Aman Harahap (RADJA PUBLIKA, 2026)
This article examines the neuroethical considerations associated with the growing use of neuromarketing in contemporary marketing practice. Advances in neuroscience and technologies such as functional magnetic resonance imaging (fMRI), electroencephalography (EEG), and eye-tracking have enabled marketers to gain deeper insights into consumers’ subconscious responses. While these developments offer significant opportunities for improving marketing effectiveness, they also raise important ethical concerns related to consumer autonomy, privacy, and potential manipulation. Using a narrative literature review, this study synthesizes insights from marketing, neuroscience, and ethics to identify key ethical themes, including the protection of autonomy, risks of exploitation, data privacy, and the need for transparency and accountability. The article further explores neuroethical risks in practice, such as misuse of neural data and ethical issues involving vulnerable populations. Based on these findings, a neuroethical framework is proposed, grounded in the principles of autonomy, beneficence, non-maleficence, and justice. This framework provides guidance for responsible research and application in neuromarketing. The study contributes by integrating ethical theory with marketing practice and offers practical implications for organizations seeking to adopt neuromarketing responsibly. Future research should focus on empirical validation and cross-cultural applications of the framework.